Transcatheter Patent Foramen Ovale Closure Is Effective in Alleviating Migraine in a 5-Year Follow-Up - He, Yao-De; Yan, Xiu-Li; Qin, Chen; Zhang, Peng; Guo, Zhen-Ni; Yang, Yi (Frontiers in Neurology, 2019)
Background: The association between patent foramen ovale (PFO) and migraine has been reported. However, whether transcatheter PFO closure is effective in alleviating migraine remains controversial. The objective of this study was to investigate the efficacy of PFO closure in alleviating migraine in a 5-year follow-up. Methods: Migraineurs with PFO from 2013 to 2015 were included and divided into PFO closure group and non-PFO closure group according to their therapy. Contrast-enhanced transcranial Doppler (c-TCD) was performed to evaluate the degree of the right-to-left shunt (RLS) and headache impact test (HIT-6) questionnaire was performed to assess the severity of migraine at 1-year and 5-year follow-up. Results: Of 193 patients, 92 patients underwent PFO closure, and 101 patients refused. The HIT-6 scores in the PFO closure group were significantly lower than the non-PFO closure group at both 1-year and 5-year follow-up. These results were more pronounced in patients younger than 45 years. Furthermore, in patients with large RLS, the HIT-6 scores of the PFO closure group were significantly lower at both 1-year and 5-year follow-up compared with the non-PFO closure group. However, in patients with moderate RLS, this difference was significant only at 5-year follow-up. Conclusions: PFO closure is effective in alleviating migraine in the long term. This effect is more obvious when patients are younger than 45 years and RLS is large.